Effectiveness of secukinumab versus an alternative TNF inhibitor in patients with axial spondyloarthritis previously exposed to TNF inhibitors in the Swiss Clinical Quality Management cohort. Issue 9 (24th June 2020) - Micheroli, Raphael; Tellenbach, Christoph; Scherer, Almut; Bürki, Kristina; Niederman, Karin; Nissen, Michael J; Zufferey, Pascal; Exer, Pascale; Möller, Burkhard; Kyburz, Diego; Ciurea, Adrian
Abstract : Objective: To compare effectiveness of treatment with secukinumab (SEC) with that of alternative tumour necrosis factor inhibitors (TNFis) in patients with axial spondyloarthritis (axSpA) after withdrawal from one or more TNFis. Methods: Patients diagnosed as having axSpA in the Swiss Clinical Quality Management cohort were included if they had initiated SEC (n=106) or an alternative TNFi (n=284) after experiencing TNFi failure. Drug retention was investigated with matching weights propensity score (PS) analyses and multiple adjusted Cox proportional hazards models. Matching weights PS-based analyses and multiple-adjusted logistic regression analyses were used to assess the proportion of patients reaching 50% reduction in the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI50) at 1 year. Results: SEC was more often used as third-line or later-line biological drug (76% vs 40% for TNFi). Patients starting SEC had higher BASDAI, Bath Ankylosing Spondylitis Functional Index, Bath Ankylosing Spondylitis Metrology Index and C reactive protein levels. A comparable risk of drug discontinuation was found for SEC versus TNFi (HR 1.14, 95% CI 0.78 to 1.68 in the PS-based analysis and HR 1.16, 95% CI 0.79 to 1.71 in the multiple-adjusted analysis). No significant difference in BASDAI50 responses at 1 year was demonstrated between the two modes of biological drug action, with CI of estimates being, however, wide (OR for SEC vs TNFi 0.76, 95% CI 0.26 to 2.18 and 0.78, 95% CI 0.24 to 2.48 in the PS-based and the covariate-adjusted model, respectively). Conclusion: Our data suggest a comparable effectiveness of SEC versus an alternative TNFi after prior TNFi exposure.